The relationship between alexithymia, hostile attribution bias, and aggression. (1st June 2020) - Li, Xu; Li, Bingbing; Lu, Jiamei; Jin, Li; Xue, Juan; Che, Xianwei
Highlights: There is a positive association between alexithymia and aggression. Different alexithymia factors did not show equally strong associations with aggression subtypes. Hostile attribution bias (HAB) moderates the link between alexithymia and aggression. HAB does not moderate the correlation between alexithymia factors and aggression subtypes. Abstract: Prior studies found a positive association between alexithymia and aggression. This study extended existing findings by adopting a subdimensional approach to investigate the unique association of alexithymia factors with reactive and proactive aggression, such as difficulty identifying feelings (DIF), difficulty describing feelings (DDF), and externally oriented thinking (EOT). This study also explored factors associated with the link between alexithymia and aggression by investigating the potential moderating role of hostile attribution bias (HAB). Four hundred and eighty-five college students (275 females) were recruited. Results showed that alexithymia was positively associated with aggression; however, different alexithymia factors did not show equally strong associations with aggression subtypes. Specifically, DIF (in contrast to DDF and EOT) was the strongest correlate of reactive aggression, while EOT (in contrast to DIF and DDF) was the strongest correlate of proactive aggression. Meanwhile, HAB was a moderator for the relationship between alexithymia and aggression, but not between alexithymia factors and aggression subtypes. Implications and limitations of the present study are discussed.